Building embodiment : integrating acting, voice, and movement to illuminate poetic text - Kelly, Baron; Kopryanski, Karen (Routledge, 2023)
"Building Embodiment: Integrating Acting, Voice, and Movement to Illuminate Poetic Text offers a collection of strategic and practical approaches to understanding, analyzing, and embodying a range of heightened text styles, including Greek Tragedy, Shakespeare, and Restoration/Comedy of Manners. These essays offer insights from celebrated teachers across the disciplines of acting, voice, and movement, and are designed to help actors find deeper vocal and physical connections to poetic text. Although each dramatic genre offers a unique set of challenges, Building Embodiment highlights instances where techniques can integrate and overlap, and illustrates how the synthesis of body, brain, and word results in a fuller sense of character experiencing for both the actor and the audience. This book bridges the gap between academic and professional application, and invites the student and professional actor into a deeper experience of character and story"--